Differential binding of Nocardia asteroides in the murine lung and brain suggests multiple ligands on the nocardial surface. - Beaman, B L (1996)
The adherence of Nocardia asteroides in the murine brain and lungs was determined. Virulent strains had increased adherence in the brain and lungs, whereas less virulent strains bound in either the brain or lungs. Nocardiae that attached apically penetrated host cells. Multiple receptors on the nocardial surface may be involved in this differential attachment and penetration.